2017
DOI: 10.5897/jphe2017.0954
|View full text |Cite
|
Sign up to set email alerts
|

Smokeless tobacco consumption among public and heavy load drivers in Karachi, Pakistan: A cross-sectional study

Abstract: Tobacco use remains a major cause of preventable morbidity and mortality worldwide. The World Health Organization states that 19.1% of the Pakistani population consumes smoked or smokeless tobacco (SLT). Although many population focused studies have focused on the use of SLT in Pakistan, but they have failed to address the use of SLT among laborers, especially the niche population of public and heavy load drivers (that is, transporters). This study aimed to estimate the prevalence of SLT consumption among this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…The study indicated a sample size of 308, which was calculated using the open EPI: software calculator with a 95% confidence level and a 5 percent error acceptable, 18 related to a prior study that revealed a prevalence rate of 64%. 19 9 th and 10 th grade male and female students age between 13 and 16 years, from selected high schools in the Taluka Qasimabad District of Hyderabad.…”
Section: Methodsmentioning
confidence: 99%
“…The study indicated a sample size of 308, which was calculated using the open EPI: software calculator with a 95% confidence level and a 5 percent error acceptable, 18 related to a prior study that revealed a prevalence rate of 64%. 19 9 th and 10 th grade male and female students age between 13 and 16 years, from selected high schools in the Taluka Qasimabad District of Hyderabad.…”
Section: Methodsmentioning
confidence: 99%